A MODEL FOR DEVELOPING SANOGENETIC THINKING IN FUTURE TEACHERS BASED ON A REFLECTIVE APPROACH - Одилова Мавлуда Учқун қизи (Bright Mind Publishing, 2025)
In connection with the development of the professional thinking of future teachers, it is recommended that the teacher use the above communication methods in a harmonious manner. Because, if the mastery of educational tasks is based on rigor, interpersonal communication is organized on the basis of a personal-humanistic approach, and a liberal style is used, creating conditions for students' independence and free thinking leads to an increase in positive achievements.
Keywords: Reflection, sanogen, motivation, Retrospective reflection, situational reflection.